2016
DOI: 10.1038/srep30822
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aflatoxins in traditional Chinese medicines: Classification of analytical method on the basis of matrix variations

Abstract: A classification system for analytical methods was developed for the first time to determine the presence of aflatoxins B1, B2, G1 and G2 in traditional Chinese medicines (TCMs) based on different matrix types using ultra-performance liquid chromatography–tandem mass spectrometry. A useful characteristic of the approach was that the TCMs could be systematically divided into four categories (i.e., volatile oils, proteins, polysaccharides and fatty oils) depending on the matrix types. The approach concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…In this study, the matrix was divided into several types (volatile oils, proteins, polysaccharides and fatty oils), and five different ratios of aqueous methanol solutions were evaluated as the extraction solvent for each type. These studies demonstrated that a 75% aqueous methanol solution was the optimal solvent for volatile oils, while a ratio of 85% was optimal for proteins and 70% for polysaccharides and fatty oils [ 79 ].…”
Section: Sampling Extraction and Cleanupmentioning
confidence: 99%
“…In this study, the matrix was divided into several types (volatile oils, proteins, polysaccharides and fatty oils), and five different ratios of aqueous methanol solutions were evaluated as the extraction solvent for each type. These studies demonstrated that a 75% aqueous methanol solution was the optimal solvent for volatile oils, while a ratio of 85% was optimal for proteins and 70% for polysaccharides and fatty oils [ 79 ].…”
Section: Sampling Extraction and Cleanupmentioning
confidence: 99%
“…Thus, it is important to consider the possibility of and test samples for multimycotoxin contaminants. For example, fruit and seeds from CHMs such as S. Armeniacae Amarum Han 2011;Han et al 2011;Zheng et al 2013;Zheng et al 2014c;Zhao et al 2016) S. Coicis Zheng et al 2010b;Xie et al 2011;Kong et al 2013;Liu et al 2013), S. Persicae Han et al 2010;Zheng et al 2010b;Han 2011;Han et al 2011;Li et al 2011a;Zheng et al 2014a) and S. Sterculiae Lychnophorae Xie et al 2011;Su et al 2014) are not only susceptible to AF contaminants but are also often cocontaminated with other mycotoxins such as OTA, ZEN, and FB. Along with a variety of methods for detecting different mycotoxins, methods for simultaneous determination for various mycotoxins have been gradually developed.…”
Section: Detection Of Multiple Mycotoxinsmentioning
confidence: 99%
“…(Continued) Yang et al 2005;Zhang et al 2008;Zheng et al 2010b;Li et al 2011a;Zhao et al 2011;Hao et al 2012;Li et al 2012;Kong et al 2013;Wang et al 2014b;Zheng et al 2014b;Zhu et al 2015;Zhao et al 2016;Chien et al 2018Yang et al 2004;Yang et al 2005;Yang et al 2011b;Hao et al 2012;Hu et al 2012;Liu et al 2012a;Hao et al 2013;Li 2015a;Zhu et al 2015;Chien et al 2018Han et al 2010;…”
mentioning
confidence: 99%
“…The World Health Organization designated AFTs as Group 1 carcinogens and they are subject to strict control worldwide (IARC Monograph, ). Foods, feed or plant‐derived Chinese herbal medicines may be contaminated by various AFTs during their growth, collection, storage and processing, resulting in a variety of AFT residues, and an increasing number of studies indicate that this should not be ignored (Cai, Gao, Li, Chen, & Li, ; Cao et al, ; Efferth & Kaina, ; Kong, Li, et al, ; Kong, Liu, Qiu, Xiao, & Yang, ; Kuang et al, ; Liu et al, ; Wei et al, ; Zhao, Zhang, Tan, Yu, & Cao, ). In view of the danger of AFTs, the USA, EU and some other countries have developed limits for AFTs in all kinds of food and medicines.…”
Section: Introductionmentioning
confidence: 99%